Financial markets and policies in East Asia - De Brouwer, Gordon (Routledge studies in the growth economies of Asia., 2002)
This book assesses the need to secure policy consistency, the scope for inflation targeting, the sustainability of exchange rate regimes and the scope for deeper financial integration in the Australasian area.